Peran Teknologi Audit dalam Mendukung Prosedur Audit Substantif pada KAP Lokal di Indonesia - Edy Susanto; Ebid Widodo; Yasri Tarawiru; Rika Rahma (Jurnal Riset Akuntansi Politala, 2026)
The rapid development of information technology has made the use of audit technology essential in the auditing profession. This requires adjustments, especially for local public accounting firms in Indonesia that rely on tools such as ATLAS and Excel, to improve efficiency, accuracy, and the ability to detect material misstatements and fraud amid the challenges of competency gaps. This study analyzes the role of audit technology in supporting substantive audit procedures, the challenges of its implementation, and strategies for adapting auditors' competencies, particularly in the context of local public accounting firms (KAP) in Indonesia. Using a qualitative approach through interviews with auditors, this study found that audit technology, such as ATLAS, plays a crucial role in enabling faster, more accurate, and comprehensive data testing, even across the entire data population. The effectiveness of clients' internal controls also directly influences the nature and scope of substantive audit procedures. This study concludes that sustained investment in audit technology and auditor competency development, coupled with effective adaptation strategies, is key to improving audit quality in the digital age, particularly in the context of local public accounting firms that differ from large-scale firms.